PENGARUH KOMPETENSI SUMBERDAYA MANUSIA TERHADAP KINERJA PEGAWAI PADA DINAS KOPERASI PERINDUSTRIAN DAN PERDAGANGAN (KOPERINDAG) KOTA BIMA - Nurrahma Wati; Ety Kurniawati (Universitas Sarjanawiyata Tamansiswa, 2020)
Competence is the basis for employees in carrying out work demands that are their responsibility. Employees must continue to improve their competencies so that they can adapt to changes related to their field of work. In this case, the organization must play a role in the development of its human resources, especially related to competencies so that future employee performance will be better. This study aims to determine the positive and significant influence of human resource competencies on employee performance at the Department of Industry and Trade Cooperatives (KOPERINDAG) of Bima City. This type of research is associative. Poulasi in this study were 50 employees with a sample of 30 employees who included ASN. The sampling technique used was purposive sampling (taking samples based on certain considerations). Data collection techniques used are observation, interviews, and questionnaires using a Likert scale, the type of data used is quantitative data from primary data sources. Data analysis techniques used are validity, reliability, simple linear regression, simple linear correlation and partial tests (T test). Based on the results of this study concludes that human resource competence does not have a significant effect on employee performance, this is evidenced by the t test value of 0.323 and sig of 0.749.Keywords: Human resource competence, employee performance